Remains of the Site of Raden Mattaher's Resistance Against Dutch Colonialism in Jambi - Asyhadi Mufsi Sadzali; Yundi Fitrah; Warni (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2020)
Jambi region which experienced resistance movements against Dutch colonialism since 1834 which was started by Sultan Taha Syafuddin continued until his death in 1904 in Betung Bedara, Tebo region, Jambi. The struggle did not stop but was continued by one of the biggest and most feared by the Dutch , his name is Raden Mattaher bin Raden Kusin. Basically, Raden Mattaher's struggle began when he joined Panglima Sultan Taha in 1885, and was even nicknamed 'Singo Kumpeh'. Raden Mattaher's involvement in several places in Jambi has left artifacts that can be used as cultural heritage, which support the handover and confirmation of Radaen Mataher as the 2nd National Hero from the Jambi region. The research method used in this research was descriptive qualitative approach and to collect the data the researcher record the data in the field to identify the relationship between artifacts and historical events. The results showed that these artifacts were closely related to the revolutionary struggle of Raden Mattaher. Keywords : History, revolutionary struggle of Raden Mattaher, artifacts.